Consensus on the definition, components, timeframe and grading of composite outcome of postoperative pulmonary complication—protocol for an international mixed-method consensus study (PrECiSIOn) - Arthur S Slutsky; Raymond Oppong; Frederique Paulus; Marcus J Schultz; Ary Serpa Neto; Sabrine N T Hemmes; Denise Battaglini; Sheila Nainan Myatra; Stijn Blot; Prashant Nasa; Timur Yurttas; Ana Fernandez-Bustamante; et al. (BMJ Open)
Introduction Postoperative pulmonary complications (PPCs) represent a significant cause of postoperative morbidity and even mortality. However, there is a lack of consensus regarding this composite endpoint, the definition of the individual components, classification and optimal outcome measures. This study aims to refine the PPCs composite framework by evaluating its construct validity, assessing the necessity and risks of a composite measure and exploring the feasibility of differentiating severity categories.Methods A Delphi consensus process will be conducted, engaging an international multidisciplinary group of 30–40 panellists, including clinicians, researchers, patients, public representatives and health economists. Through iterative rounds, the study will seek agreement on the individual components of the PPCs composite. Additionally, consensus will establish a framework for a composite outcome measure based on a standardised severity classification, appropriate timeframes and weighted grading of PPCs.Analysis Consensus, defined by ≥75% concurrence in multiple choice questions or on Likert–scale statements, will be evaluated from round 2 onwards. Delphi rounds will be continued until all statements have reached stability of responses evaluated by χ2 tests or the Kruskal-Wallis test.Ethics and dissemination The study will be conducted in strict compliance with the principles of the Declaration of Helsinki and will adhere to ACCORD guidance for reporting. Ethics approval has been obtained for this study from the University of Wolverhampton, UK (SOABE/202425/staff/3). Informed consent will be obtained from all panellists before the commencement of the Delphi process. The results of the study will be published in a peer–reviewed journal with the authorship assigned in accordance with ICMJE requirements.Trial registration number NCT06916598 (clinicaltrials.gov).